2014
DOI: 10.1177/1934578x1400900435
|View full text |Cite
|
Sign up to set email alerts
|

ETAS, an Enzyme-treated Asparagus Extract, Attenuates Amyloid β-Induced Cellular Disorder in PC 12 Cells

Abstract: One of the pathological characterizations of Alzheimer's disease (AD) is the deposition of amyloid beta peptide (A) in cerebral cortical cells. The deposition of Ain neuronal cells leads to an increase in the production of free radicals that are typified by reactive oxygen species (ROS), thereby inducing cell death. A growing body of evidence now suggests that several plant-derived food ingredients are capable of scavenging ROS in mammalian cells. The purpose of the present study was to investigate whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…A recent study also showed that ETAS 50 supplementation reduced the feelings of dysphoria and fatigue, ameliorated the quality of sleep, and enhanced stress-load performance as well as increasing salivary secretory immunoglobulin A levels in healthy adults [ 16 ]. In addition to these anti-stress effects, ETAS 50 has antiaging potencies via its ability to ameliorate cognitive impairment in senescence-accelerated mice [ 17 ], to protect neuronal PC-12 cells from amyloid β peptide-induced oxidative stress and cytotoxicity [ 18 ], and to improve learning ability in young healthy rats [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also showed that ETAS 50 supplementation reduced the feelings of dysphoria and fatigue, ameliorated the quality of sleep, and enhanced stress-load performance as well as increasing salivary secretory immunoglobulin A levels in healthy adults [ 16 ]. In addition to these anti-stress effects, ETAS 50 has antiaging potencies via its ability to ameliorate cognitive impairment in senescence-accelerated mice [ 17 ], to protect neuronal PC-12 cells from amyloid β peptide-induced oxidative stress and cytotoxicity [ 18 ], and to improve learning ability in young healthy rats [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a unique eco-friendly functional food that attenuates sleep deprivation-induced stress responses, promotes good sleep, and increases salivary secretory immunoglobulin A levels in mice and humans [ 13 15 ]. In addition to its antistress effects, later studies demonstrated the beneficial effects of ETAS 50 on brain functions, including the ability to ameliorate cognitive impairment in senescence-accelerated mice [ 16 ], protect neuronal PC-12 cells from amyloid β -induced cytotoxicity [ 17 ], and improve learning ability in young healthy rats [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroprotection due to antioxidative effects could be another mechanism contributing to results observed in this clinical trial. In an in vitro cell study by Ogasawara et al 2014, asparagus extract was shown to scavenge the negative effect of free radicals at the cellular level [53]. In another study, asparagus extract was demonstrated to enhance expression of cytoprotective factors such as heat shock transcription factor 1 (HSF1) and Nrf2 protein [54].…”
Section: Discussionmentioning
confidence: 99%